152 Supplemental effects of chelated trace minerals replacing inorganic trace minerals in sow diets on production performance, DNA methylation, histone acetylation, and gene expression in muscle and intestinal tissues of progeny. (7th December 2018) - Jang, K; Kim, J; Purvis, N; Purvis, J; Chen, J; Ren, P; Vazquez, M; Kim, S
Abstract: Changes in maternal nutrition may cause epigenetic regulation in tissues of fetus. The objective of this study was to determine the supplemental effects of chelated trace minerals replacing inorganic trace minerals in sow diets on growth, global DNA methylation, histone acetylation, gene expression in muscle and intestinal tissues of progeny. On d 35 of gestation, 60 pregnant sows were allotted to 2 dietary treatments in randomized completed block design using parity as a block. Two treatments were (1) ITM: CuSO4, MnO, and ZnSO4 and (2) CTM: inorganic Cu, Mn, and Zn + chelated Cu [Cu (HMTBa, 2-hydroxy-4-methylthio butanoic acid)2 ], Mn [Mn (HMTBa)2 ], Zn [Zn (HMTBa)2 ] (MINTREX®), Novus International Inc.) at the ratio of 1:1. The gestation and lactation diets were formulated to meet or exceed nutrient requirements suggested by NRC (2012). On d 1 and d 18 of lactation, two pigs per litter were euthanized to collect longissimus dorsi muscle, and jejunum tissues to measure global DNA methylation, histone acetylation, and gene expression. Data were analyzed using the MIXED procedure of SAS. Sows fed CTM tended to decrease ( P = 0.059) BW loss during lactation and tended to increase ( P = 0.098) piglet BW on d 18 of lactation. Sows fed CTM did not affect global DNA methylation in jejunum and longissimus dorsi muscle of piglets at birth and d 18 of lactation. However, CTM increased ( P < 0.05) global histone acetylation, tended to decrease ( P = 0.072) MYF4 mRNA in muscle of piglets at birth, and decreased ( P < 0.05) jejunal NF-kB mRNA in piglets on d 18 of lactation. In conclusion, supplementation of chelated trace minerals in the form of MINTREX® could potentially improve sow BW condition during lactation and enhance intestinal health and muscle growth in piglets, therefore leading to better growth performance of piglets.